Post content and its effect on consumer engagement rate in Indian life insurance Facebook brand pages - Jayasingh, Sudarsan; Thiruvenkadam, T.; Arunkumar, S. (International Journal of Engineering and Technology, 2018)
Indian insurance companies are new in adopting social media marketing and this research paper try to identify the post characteristics that drive consumer engagement in Facebook brand pages. The data used for this study was obtained from the post of five brands of Indian life insurance companies’ official Facebook brand pages. The data collection was gathered using Fanpage Karma over a period of three months, from the 1st of Jan to the 31st of March 2017. The posts collected during the period were 448 brand-initiated posts in total. This study calculated consumer engagement rate as total number of likes, comments and shares by total number of fans. The analysis is done using negative binomial regression statistical technique. The results show that media format and content type significantly affects the consumer engagement in Facebook brand pages. Content that provides brand related information was found to be one of important factor to increase the consumer engagement rate. The consumer engagement is found to be high for images of low vividness. The recommendations provided to marketers based on the research findings in this study.